The Role of MGMP in Improving Teacher Professionalism at State Junior High School 10 Padang - Putri, Sri Wati; Nelwati, Sasmi; Albizar, Albizar (Khalaqa: Journal of Education and Learning, 2025)
This study aims to describe the role of Subject Teachers' Consultative Meeting (MGMP) in improving teacher professionalism at State Junior High School 10 Padang. Teacher professionalism includes pedagogical, professional, social, and personality competencies that are essential in supporting the quality of education. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews with teachers who actively participate in MGMP activities. The results of the study indicate that MGMP plays an important role as a forum for developing teacher competencies through various activities such as training, discussions, and workshops. These activities have been proven to support the improvement of teachers' abilities in designing learning, implementing innovative methods, and conducting learning evaluations effectively. Thus, MGMP has a real contribution in improving teacher professionalism and the quality of the learning process in schools.